Influência de polimorfismos em genes que codificam citocinas pró-inflamatórias bem como de marcadores de virulência de H. pylori nas concentrações gástricas das citocinas em crianças e adultos - Fabrício Freire de Melo (2007)
We evaluated the concentrations of IL-1, IL-1, IL-8, and TNF- in the gastric mucosa of Helicobacter pylori-negative and -positive children (n = 143) and adults (n = 143). The groups as well as subgroups of cagA/vacA positive subjects were compared. The levels of cytokines in H. pylori positive groups were also compared based on the bacterium cagA gene and vacA mosaicism status. The influence of the IL1B, IL1RN, and TNFA polymorphisms on the expression of gastric mucosa cytokines was also evaluated. H. pylori infection was diagnosed by culture, histology and preformed urease test. cagA and vacA status were investigated by PCR. Polymorphism of the genes IL1B at -31 and -511 positions, IL1RN (variable number tandem repeats) and TNFA at -307 position were evaluated by PCRCTPP, PCR-RFLP, PCR, and PCR-RFLP, respectively. The results were confirmed by sequencing. Cytokine concentrations were determined in a fragment of gastric antral mucosa by immunoenzymatic assay. The results were presented as mean ± standard deviation. Since the data did not show a normal distribution according to the Kolmogorov-Smirnov test, they were converted in logarithm, after which they showed normal distribution. The cytokine levels between the groups were compared by Students t test. The differences were considered statistically significant when p 0.05. Among the children, 76 were H. pylori-negative and 67 were H. pylori-positive. Forty two adults were H. pylori negative and 101 were H. pylori positive. The mean levels of IL-1, IL-1, IL-8, and TNF- in the H. pylori infected children and adults were significantly higher than in those H. pylori negative. The levels of IL-1 and TNF- in the group of bacterium-infected patients were higher in the children than in the adults. The levels of IL-1 were higher in the adults than in the children, regardless of the H. pylori status. The mean concentration of IL-8 was significantly higher in the groups of cagApositive patients than in those of -negative ones. Similar results were observed in respect to s1m1 vacA genotype. This association; however, disappeared when the data were corrected for the cagA status. No association between cytokine gastric levels and IL1B, IL1RN and TNFA polymorphisms was observed in the H. pylori-negative children and adults. On the other hand, we demonstrated, for the first time, that the concentration of IL-1b, but not IL-1a, was higher in the gastric mucosa of patients harboring the polymorphic alleles of IL1RN than in those with the wild allele.